"A REPRESENTAÇÃO DOS PAPÉIS E DA SEXUALIDADE FEMININA NO TEATRO BRASILEIRO DURANTE O PERÍODO DA DITADURA MILITAR” - Pelegrini, Sandra C. A (2007)
The expansion of the methodological universe of History gave way to a wide diversity of studies in the field of gender research. In this context, the article aims to investigate the social representations portrayed in the dramaturgical production of Leilah Assunção between 1968 and 1970, a period in which changes were brought about in the structure of the Brazilian theater. Through the analysis of the dramaturgical discourse of the theatrical works “Use Polvo de Arroz Bijou” and “Hable Bajo, si no yo grito”, the author makes evident the social tensions arising in the midst of the military dictatorship in Brazil, and the discussions on the role and sexuality of women in the private and public scope